Management of breast cancer risk in BRCA1/2 mutation carriers who are unaffected with cancer. Issue 8 (11th July 2020) - Collins, Julie M.; Isaacs, Claudine
Abstract: Pathogenic mutations in BRCA1 and BRCA2 genes markedly increase the risk of breast cancer and other cancers such as ovarian/fallopian tube, pancreatic, prostate, and melanoma. Patients with BRCA1 mutations have a slightly higher lifetime risk of breast cancer than BRCA2 mutation carriers, and both BRCA1 and BRCA2 carriers tend to develop breast cancer at an earlier age than the general population. In this review, we will discuss management recommendations to reduce breast cancer risk for BRCA1/2 mutation carriers including special populations of carriers such as pregnant or lactating patients and men. Breast cancer screening, including clinical breast examination, mammogram, and breast MRI, is important for detecting breast cancer at an early and likely curable stage. In addition to screening, counseling on risk‐reducing surgeries is strongly recommended for BRCA1/2 carriers. Risk‐reducing mastectomy decreases the risk of breast cancer development, and risk‐reducing salpingo‐oophorectomy decreases ovarian cancer‐specific as well as overall mortality, but controversy exists regarding its impact on breast cancer‐specific mortality. Given the effectiveness of screening for breast cancer, further management should be carried out on an individual basis taking into account quality of life and psychosocial factors, and recommendations should be readdressed periodically as science progresses and patients' goals may change.